THE USE OF MONDLY APPLICATION AS A MEDIA TO INCREASE STUDENTS’ WRITING ABILITY AT SECOND GRADE SD INPRES TETEBATU - Juriati, Juriati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The aim of this research is to know the improvement of students’ writing ability by the implementation of Mondly Application. The research applies pre-experimental with one grup class pre-test and post-test. This research was conducted at SD Inpres Tetebatu. In this research the population was the eight students of SD Inpres Tetebatu in 2021/2022 academic year. The researcher used total sampling technique. The total number of samples was 26 students from class II. After conducted the research, the researcher concludes that the used of mondly application increase writing skill student, it is proved by the mean score of the students in pretest and post-test. The result of the research shows that Mondly application significantly increase students’ writing ability after did treatment. mean score improved from 334 in pre-test to 510,75 in post-test. It indicated that the alternative hypothesis (HA) was accepted and, of course, the null hypothesis (H0) was rejected. It means that Mondly Application could increase the students’ Writing ability in learning English at SD Inpres Tetebatu.